PENGARUH LKPD BERBASIS PROYEK TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Niken Azzahra; Dayu Rika Perdana; Roy Kembar Habibi; Herpratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to determine the effect of using project-based Student Worksheets (LKPD) on the improvement of critical thinking skills among fourth-grade students at SD Negeri 3 Way Galih in the Civic Education learning process. The background of this research was based on the low critical thinking abilities of the students, as evidenced by the average pretest scores of 51.61% for class IV A and 46.31% for class IV B. This research employed a quantitative approach with a quasi-experimental design. The instrument used was a critical thinking test based on Ennis's indicators. The analysis results indicated a significant improvement in the experimental group, with an average pretest score of 19.88 and a posttest score of 35.42. Meanwhile, in the control group, the average pretest score was 23.13 and the posttest score was 30.04. These findings demonstrated that the use of project-based LKPD was effective in enhancing the critical thinking skills of elementary school students.